Management innovation and competitiveness from public policy in Costa Rica - Sandoval Barraza, Azucena (2016)
Science, technology and innovation developed by enterprises, are crucial to the economic development of the regions factors. Therefore, the study analyzes the management mechanisms of innovation in a broad sense, according to the OECD (2011) from the results-based approach, behavior and changes so that it constitutes a valuable tool for the competitiveness of enterprises.